Predictors of Maternal Near Miss in Public Hospitals of West Shoa Zone, Central Ethiopia: A Case-Control Study - Danusa, Kababa Temesgen; Debelo, Bikila Tefera; Wakgari, Negash; Seifu, Benyam; Kenasa, Ketema; Daba, Gurmesa; Wondimu, Fikadu; Berhanu, Keneni (Frontiers in Medicine, 2022)
Background: Maternal mortality reduction remains a priority to ensure healthy lives and promote well-being for mothers and newborns in the new sustainable development goals agenda. There is no evidence-based study done regarding maternal complications and near-miss in the study area. Objectives: This study assessed the predictors of maternal near-miss in public hospitals of West Shoa Zone, Central Ethiopia, 2020. Methods: An unmatched case-control study was conducted among 664 (166 cases and 498 controls) women who gave birth in public institutions of the West Shewa zone. Structured questionnaires and checklists were used to collect the data. Bivariate, multivariable logistic regression, and adjusted odds ratios were used to describe the strength and directions of association. Results:- The odds of maternal near-miss were higher among mothers with increased maternal age [AOR=1.065, 95%CI(1.015-1.117)], who could not read and write (AOR=3.06, 95%CI:1.314-7.135), had primary (AOR=3.49, 95%CI:1.518-8.044), and secondary (AOR=3.213, 95%CI:1.418-7.282), had no ANC follow-up (AOR=2.25, 95%CI: 1.100-4.607), mothers who had a first delay of >6 hours [AOR=2.38, 95%CI (1.517-3.735)] and the distance from health facility of >60 minutes [AOR=4.021, 95%CI (1.817-8.896)]. Conclusions: In this study, delay in decision making and reaching the health facility, lower educational status, not having ANC follow-up, and increased maternal age were significantly associated with maternal near misses. Therefore, the Ethiopian federal ministry of health and other stakeholders should work on increasing ANC coverage, awareness creation, and strong means of transportation to tackle the complications of a maternal near miss.